The Phonetic, Grammatical, and Semantic Structure of Professor Sharma’s Diary Poem - Gautam, Tulasi Prasad (Adhyayan Journal, 2023)
This research paper presents a structural analysis of the poet BiplavDhakal's poem Professor Sharma's Diary. Structuralism is a movement that arose in the intellectual activity of Europe and France during the 1950s and 1960s of the 20th century. It is a system devised in the fields of language, culture, society, and literature, among others. In this method, when studying literature, neither society, culture, politics, history, etc. outside the work are studied, but rather the structural components of the work's creation and their mutual relationship are. While studying a work, it has developed the practice of objectively criticizing it by analyzing its form-structure, linguistic structure, environment (country, time, and circumstance), etc. Therefore, the meaning of the above-mentioned critical poem has been conveyed through structural analysis. Since attempting to encompass the breadth of knowledge in a limited diary is fundamentalism, it has been determined that the current teaching method should be revised and a new knowledge horizon should be established. It has established BiplavDhakal as a visionary poet capable of expressing contemporary issues in poetry effectively.